Psychometric properties of the scale for measuring beliefs that perpetuate intrafamilial violence in Peruvian women - Huamani-Cahua, Julio (2024)
Introduction: The couple violence is a phenomenon with relevant social and health implications for the victims, and requires validated instruments for its application in forensic context. Objective: The present study has as aim to analyze the psychometric properties of the Scale for Measuring Beliefs that Perpetuate Intrafamiliar Violence. Method: A sample of 1977 women from Arequipa (in Peru) were selected by mean of non-probabilistic methods. Results: The results has confirmed the three factors structure of the Scale for Measuring Beliefs that Perpetuate Intrafamiliar Violence, by confirmatory factor analysis, that count with optimal reliability indexes: Disturbing beliefs of physical maltreatment (ω= .895), Disturbing beliefs of domestic violence (ω= .865), and Disturbing beliefs of sexual abuse in minors (ω= .848). Conclusion: It is concluded that the Scale for Measuring Beliefs that Perpetuate Intrafamiliar Violence has evidence of validity and reliability.